A conspiracy to murder: explaining the dynamics of Romanian 'policy' towards Jews in Transnistria. Issue 1 (2nd January 2017) - Solonari, Vladimir
ABSTRACT: This article offers a comprehensive interpretation of the Romanian 'policy' towards Jews in Transnistria in 1941–44. This region in southwestern Ukraine witnessed both a monstrous number of Jewish victims, usually estimated as no fewer than 350, 000 and possibly more, and an unusually high survival rate by the standards of the occupied Soviet territory. The article argues that what is sometimes referred to as 'inconsistency' in Romanian policy can be best explained within the framework of the structuralist/functionalist approach to the history of the Holocaust that was first developed on German material. The article argues that Romanian leaders never adopted the policy of complete annihilation of Jews; rather, their aim was to expel them from Romania's national territory. However, they were not opposed to murdering Jews en masse when they believed it was 'necessary' from a military point of view or advisable for any other reason. Given the scarcity of resources in the region and the fear of epidemics, murdering interned Jews in the areas of their greatest concentration appeared to be the way to 'solve' a number of problems. At the same time, the absence of a fanatical paramilitary force such as the SS in Nazi Germany and Romanian leaders' unwillingness to leave a paper trail of their criminal orders complicated the logistics of mass murder. Mass murder required either the ready participation of the gendarmerie and police, which was not always forthcoming, or the mobilization of the ethnic German militia, which was not available everywhere. In the absence of pressure from the authorities to kill, some officers and individual gendarmes, cognizant of the criminal nature of such actions, hesitated or even avoided participation in mass murder.